Second-Order Innovation: Modeling the Context of Invention: Lights on Italy in the Sixties - Carradore, Roberto; Tonoli, Matteo; Cerroni, Andrea (Journal of Sociocybernetics, 2020)
The aim of this contribution is to consider Italy during the Sixties in order to model contemporary innovation dynamics. The purpose is not only for collective memory retrieval but mainly for de-constructing the innovation circuit and re-constructing it by means of a more sophisticated and detailed frame. A glossary of eigenvalues will be suggested through the concepts of garbo, cenacolo and pollinator; moreover, this glossary will be tested in two case studies: Olivetti and Bialetti. Starting from a simpler and circumscribed innovation regime, the final objective is to supply theoretical tools and support policy design in the actual “dark age”, where the message is drawn in a sea of noise and people start to confuse hoaxes with signals, thus polluting the communication and forcing a causal interpretation of casual relationships.